Multifunctional shrinkage-reducing self-expanding rheological agent for spraying ultra-high performance concrete
By using composite rheological components, expansion components and anti-corrosion reduction components in sprayed ultra-high performance concrete, the problems of insufficient thixotropy and self-contraction of UHPC are solved, and its yield stress and durability are improved, especially in the ocean In the engineering environment, rust and shrinkage are effectively reduced and construction performance is improved.
Patent Information
- Application Number
- CN202411048866.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-01
AI Technical Summary
In construction, sprayed ultra-high performance concrete (UHPC) has problems such as insufficient thixotropy, large self-contraction and internal corrosion, which affects its strength and durability, and is more prominent in marine engineering or humid environments.
The multifunctional reduction self-expanding rheological agent is prepared using composite rheological components, expansion components and anti-corrosion reduction components, including the composite rheological components of manganese slag and cellulose ether, and the expansion of modified calcium oxide-calcium sulfaaluminate Components and bimetallic hydroxide-loaded biofilm anti-corrosion reduction components to improve UHPC's thixotropy, shrinkage performance and durability.
By improving the rheological properties and matrix compactness of UHPC, reducing self-shrinkage and rust, it significantly improves its yield stress, anti-chlorine ion penetration performance and durability, and improves the sprayability and mechanical properties of jet construction.
Smart Images

Figure CN119161124A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a multifunctional shrinkage-reducing self-expansion rheological agent for sprayed ultra-high performance concrete (UHPC), in particular to a multifunctional shrinkage-reducing self-expansion rheological agent suitable for sprayed ultra-high performance concrete with insufficient thixotropy and large self-shrinkage. Background Art
[0002] With the continuous development of economy and the advancement of science and technology, human beings are constantly exploring the fields of high altitude, underground and ocean. Modern civil engineering pays more attention to the development trend of high-rise, light and large span. Ultra-high performance concrete (UHPC) is a new type of building material with excellent mechanical properties and high impermeability, which makes UHPC a building material that meets the above strategic requirements. In order to increase the scope of application of UHPC in actual engineering, UHPC is used in spraying construction as a material for the renovation, repair and reinforcement of damaged buildings. The spraying of UHPC requires increasing the yield stress to reduce the rebound of the slurry and increase the thickness of the sprayed concrete layer, and the slurry should maintain a low plastic viscosity to improve pumpability. The high yield stress and low plastic viscosity of concrete can be expressed by thixotropy. UHPC is a typical non-Newtonian fluid with certain thixotropy, but the thixotropy of the newly mixed UHPC is not enough to support high-thickness spraying construction. At the same time, UHPC has a high content of cementitious materials, which causes its shrinkage to be much greater than that of ordinary concrete. It may cause cracks on the surface or inside of the concrete, reducing its strength and durability. In marine engineering or humid environments, UHPC containing steel fibers is often corroded by chloride ions, causing the steel fibers to rust or the concrete matrix to corrode, affecting its performance and appearance. Summary of the invention
[0003] The purpose of the present invention is to provide a multifunctional shrinkage-reducing self-expanding rheological agent for sprayed ultra-high performance concrete (UHPC), which can be prepared by using a composite rheological component, an expansion component and an anti-corrosion shrinkage-reducing component to improve the thixotropy, shrinkage performance and durability of UHPC.
[0004] The technical solution adopted by the present invention to solve this technical problem is: a multifunctional shrinkage-reducing self-expansion rheological agent for sprayed ultra-high performance concrete, comprising a composite rheological component, an expansion component and an anti-corrosion shrinkage-reducing component;
[0005] Among them, the composite rheological component is 65 to 87 parts, the expansion component is 10 to 30 parts, and the anti-corrosion and shrinkage-reducing component is 3 to 5 parts.
[0006] As a further solution of the present invention, it is composed of a composite rheological component, an expansion component and an anti-corrosion and shrinkage-reducing component.
[0007] As a further embodiment of the present invention, the composite rheological component includes manganese slag and cellulose ether;
[0008] The composite rheological component is added in an amount of 5-10% of the cementitious material. The cementitious material is generally cement, or cement plus mineral admixtures, such as cement, fly ash, silica fume, slag, etc. The ratio of manganese slag to cellulose ether is 98:2, and the specific surface area of the manganese slag is 600-800m 2 / kg; cellulose ether is hydroxyethyl methyl cellulose ether, with a molecular weight of 30,000 to 50,000. Too low a molecular weight will reduce the mutual entanglement between molecular chains, resulting in poor viscosity enhancement effect. Too high a molecular weight will cause macromolecules to excessively entangle and wrap around cement particles, hindering the dissolution of cement particles, thereby inhibiting cement hydration and reducing the strength of concrete. The composite rheological components are used to improve the rheological properties and matrix density of concrete mixtures, and to enhance the sprayability and mechanical properties of sprayed UHPC.
[0009] As a further solution of the present invention, the expansion component is a modified calcium oxide-calcium sulfoaluminate expansion agent, which is prepared by calcium oxide and calcium sulfoaluminate in a ratio of 7:3. Calcium sulfoaluminate participates in hydration or reacts with cement hydration products to form trisulfur type hydrated calcium sulfoaluminate (ettringite). The formation of ettringite greatly increases the solid phase volume, and calcium oxide crystals hydrate with water to form calcium hydroxide crystals, which increase in volume, thereby causing the apparent volume expansion to decrease the shrinkage of UHPC caused by cement hydration or water evaporation.
[0010] As a further embodiment of the present invention, the anti-corrosion and shrinkage-reducing component is a double-layered hydroxide (LDHs) loaded biofilm, such as Figure 1 As shown, the LDHs-loaded biofilm adsorbs harmful anions (such as Cl - 、SO4 2- ), reduce steel fiber corrosion and erosion of the concrete matrix, improve concrete durability, improve LDHs dispersion through biofilm, and at the same time reduce shrinkage stress and reduce concrete shrinkage.
[0011] As a further solution of the present invention, the preparation method of the double metal hydroxide (LDHs) loaded biofilm is:
[0012] S1. The biofilm is formed by bacteria on various surfaces by synthesizing and secreting a cohesive and protective cell matrix. Preparation of biofilm;
[0013] S2. Heat the biofilm in water to 70 to 85°C, then add M 3+ Solution and M 2+ solution, then adding NaOH solution to adjust the pH to 11-12, stirring thoroughly, centrifuging, washing to neutrality, and drying to obtain a double metal hydroxide (LDHs) loaded biofilm; wherein the M3+ The solution includes FeCl3, AlCl3 and CoCl3, M 2+ The solution includes CaCl2, MgCl2 and ZnCl2.
[0014] In one preferred embodiment, the specific method of loading the biofilm with LDHs is as follows: taking a number of biofilms and placing them in a beaker containing 2.0L distilled water and heating them until the water temperature stabilizes at about 80°C; preparing 0.1mol·L -1 M 3+ Solution (FeCl3, AlCl3, CoCl3) and 0.2 mol·L -1 M 2+ Solution (CaCl2, MgCl2, ZnCl2), take 200ml of each and add them to the beaker containing the original biofilm, and add 10% NaOH solution to adjust the pH to about 11-12, and stir vigorously for 4h; take out the stirred substrate and rotate it at a speed of 1000-1500r·min -1 The solid was centrifuged for 10 min under the conditions of ; the solid obtained after centrifugation was washed to make its pH neutral, and placed in an oven to dry for 16 h to obtain the LDHs-loaded biofilm.
[0015] As a further scheme of the present invention, the preparation of the biofilm in S1 specifically includes: inoculating frozen Bacillus subtilis into 15 ml Luria / Miller LB-Medium liquid at 37°C±2°C overnight; then transferring the culture to a shaking incubator (250 rpm) to grow for 12±1 hours, and then smearing the liquid culture on an agar plate enriched with LBPlus medium to allow the Bacillus subtilis liquid culture to produce a biofilm on the agar plate. After growing for at least 24 hours, the biofilm is scraped from the culture dish with a rubber scraper.
[0016] The present invention has at least the following beneficial effects: The present invention provides a multifunctional shrinkage-reducing self-expansion rheological agent for sprayed ultra-high performance concrete (UHPC), which effectively solves the problems of insufficient thixotropy, large shrinkage and internal corrosion of UHPC. Specifically, it is:
[0017] (1) The rough surface of manganese slag particles can increase the friction within the slurry and improve the slurry yield stress. After being compounded with cellulose ether, it can disperse the cellulose ether for the first time, improve the dispersion effect of the secondary dispersion of cellulose ether in the gelling material, and reduce the degradation of the strength of UHPC by cellulose ether.
[0018] (2) Compensate for UHPC shrinkage through special expansion components and improve UHPC volume stability. Anhydrous calcium sulphoaluminate can quickly start hydration reaction in the plastic stage to generate expansive hydration product ettringite. Subsequently, the hydration reaction rate of calcium oxide gradually increases in the coagulation and hardening stage to generate expansive hydration product calcium hydroxide, which together with ettringite, compensates for UHPC shrinkage.
[0019] (3) The shrinkage stress in the concrete capillaries is reduced by anti-corrosion shrinkage-reducing components, which reduces the shrinkage of UHPC caused by cement hydration or water evaporation, while effectively absorbing harmful anions (such as Cl - 、SO4 2- ), reduce the rust of steel fibers and the erosion of concrete matrix, and improve the durability of concrete.
[0020] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a diagram of the LDHs-loaded biofilm and the LDHs molecular structure of the present invention;
[0022] Figure 2 It is a schematic diagram of the capillary pore wall and pore water of the present invention. DETAILED DESCRIPTION
[0023] The present invention is described in detail and completely in conjunction with the embodiments below. Those skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention in conjunction with the embodiments, it should be particularly noted that the technical solutions and technical features provided in each part of the present invention, including the following description, can be combined with each other without conflict.
[0024] In addition, the embodiments of the present invention involved in the following description are generally only a part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0025] The present invention is further described in detail below in conjunction with the accompanying drawings and implementations, and its specific implementation process is as follows:
[0026] This paper provides a method for preparing a multifunctional shrinkage-reducing self-expanding rheological agent for sprayed ultra-high performance concrete (UHPC). First, the thixotropic properties of UHPC are improved by composite rheological components to enhance its sprayability. Secondly, the expansion component is used to reduce the shrinkage of UHPC. Finally, the anti-corrosion shrinkage-reducing component is used to reduce the surface tension of the liquid phase in the concrete capillary, so that the negative pressure in the capillary decreases, the shrinkage stress is reduced, the concrete shrinkage is reduced, and the dispersion of LDHs is improved, which effectively adsorbs harmful anions (such as Cl - 、SO4 2- ), reduce the corrosion of steel fibers and the erosion of concrete matrix, and improve the durability of concrete. The multifunctional shrinkage-reducing self-expansion rheological agent for sprayed UHPC prepared by the above method effectively solves the problems of insufficient thixotropy, large shrinkage and internal corrosion of sprayed UHPC.
[0027] A method for preparing a multifunctional shrinkage-reducing self-expansion rheological agent for sprayed ultra-high performance concrete (UHPC), specifically comprising:
[0028] (1) The multifunctional shrinkage-reducing self-expanding rheological agent is composed of a composite rheological component, an expansion component and an anti-corrosion shrinkage-reducing component, wherein the composite rheological component is 65 to 87 parts, the expansion component is 10 to 30 parts, and the anti-corrosion shrinkage-reducing component is 3 to 5 parts.
[0029] (2) The composite rheological component is composed of manganese slag and cellulose ether, and the amount of the composite rheological component is 5-10% of the cementitious material. The cementitious material is generally cement, or cement plus mineral admixtures, such as cement, fly ash, silica fume, slag, etc. The ratio of manganese slag to cellulose ether is 98:2, and the specific surface area of the manganese slag is 600-800m 2 / kg; cellulose ether is hydroxyethyl methyl cellulose ether, with a molecular weight of 30,000 to 50,000. Too low a molecular weight will reduce the mutual entanglement between molecular chains, resulting in poor viscosity enhancement effect. Too high a molecular weight will cause macromolecules to excessively entangle and wrap around cement particles, hindering the dissolution of cement particles, thereby inhibiting cement hydration and reducing the strength of concrete. The composite rheological components are used to improve the rheological properties and matrix density of concrete mixtures, and to enhance the sprayability and mechanical properties of sprayed UHPC.
[0030] (3) The expansion component is a modified calcium oxide-calcium sulfoaluminate expansion agent, which is prepared by calcium oxide and calcium sulfoaluminate in a ratio of 7:3. Calcium sulfoaluminate participates in hydration or reacts with cement hydration products to form trisulfur hydrated calcium sulfoaluminate (ettringite). The formation of ettringite greatly increases the solid phase volume. Calcium oxide crystals hydrate with water to form calcium hydroxide crystals, which increase in volume, thereby causing the apparent volume expansion to decrease the shrinkage of UHPC caused by cement hydration or water evaporation.
[0031] (4) The anti-corrosion and shrinkage-reducing component is a double-layered hydroxide (LDHs) loaded biofilm, such as Figure 1 As shown, the LDHs-loaded biofilm adsorbs harmful anions (such as Cl - 、SO4 2- ), reduce steel fiber corrosion and erosion of the concrete matrix, improve concrete durability, improve LDHs dispersion through biofilm, and reduce shrinkage stress and concrete shrinkage. The preparation method is:
[0032] S1; The biofilm is formed by bacteria on various surfaces by synthesizing and secreting a cohesive and protective cell matrix. The preparation of the biofilm is as follows: First, the frozen Bacillus subtilis is inoculated into 15 ml Luria / Miller LB-Medium liquid and grown overnight at 37°C. Next, the culture is transferred to a shaking incubator (250 rpm) and grown for 12 hours, after which the liquid culture is spread on an agar plate rich in LBPlus medium, so that the Bacillus subtilis liquid culture produces a biofilm on the agar plate. After 24 hours of growth, the biofilm is scraped from the culture dish with a rubber scraper.
[0033] S2; The specific method of LDHs loading biofilm is: take some biofilms and place them in a beaker containing 2.0L distilled water and heat until the water temperature stabilizes at around 80°C; prepare 0.1mol·L -1 M 3+ Solution (FeCl3, AlCl3, CoCl3) and 0.2 mol·L -1 M 2+ Solution (CaCl2, MgCl2, ZnCl2), take 200ml of each and add them to the beaker containing the original biofilm, and add 10% NaOH solution to adjust the pH to about 11-12, and stir vigorously for 4h; take out the stirred substrate and rotate it at a speed of 1000-1500r·min -1 The solid was centrifuged for 10 min under the conditions of ; the solid obtained after centrifugation was washed to make its pH neutral, and placed in an oven to dry for 16 h to obtain the LDHs-loaded biofilm.
[0034] (5) The LDHs are usually packed in dense layers, such as Figure 1 As shown in the figure, it is easy to form dense particles or blocks, resulting in low hydraulic conductivity, limited exposed active sites and significantly reduced adsorption performance in practical applications. LDHs can be effectively dispersed through biofilms and their adsorption performance can be enhanced.
[0035] (6) The biofilm can reduce surface tension. The contact angle between the biofilm and water is 143°. Usually, the contact angle between the capillary wall and water is 0°. Therefore, when the capillary pores lose water, the biofilm can reduce the capillary pore pressure and reduce the shrinkage of concrete. The schematic diagram of pore water and pore wall is shown in Figure 2 As shown, the capillary pressure calculation formula is as shown in Formula 1.
[0036]
[0037] In formula (1): σ is the capillary pressure (MPa);
[0038] γ is the surface tension (N);
[0039] θ is the water contact angle of the capillary wall;
[0040] r is the hole radius.
[0041] Example 1 is a concrete with a multifunctional shrinkage-reducing self-expanding rheological agent. The concrete mix ratio of Example 1 is shown in Table 1.
[0042] Table 1 Concrete mix ratio table of Example 1 (kg / m 3 )
[0043]
[0044]
[0045] The raw materials described in Example 1: cement uses PO 52.5 ordinary silicate cement, fly ash, silica ash quartz powder, quartz sand, steel fiber, and water reducer all use commercial products that meet the requirements, and the water reduction rate of the water reducer is 18%; the ratio of the composite rheological component, the expansion component and the anti-corrosion shrinkage reduction component in the multifunctional shrinkage reduction self-expansion rheological agent is 66:30:4, the composite rheological component is manganese slag and cellulose ether in a ratio of 98:2, the expansion component is calcium oxide-calcium sulfoaluminate, and the anti-corrosion shrinkage reduction component is LDHs loaded biofilm. The amount of each component is shown in Table 1. The raw materials used in Comparative Example 1 are the same as those in Example 1, but the multifunctional shrinkage reduction self-expansion rheological agent is not added. The results of the rheological properties, 7d shrinkage and chloride ion penetration resistance of UHPC are shown in Table 2.
[0046] Table 2 Results of plastic viscosity, yield stress, 7d shrinkage, chloride ion permeability coefficient and thixotropic value of UHPC in Example 1 and Comparative Example 1
[0047]
[0048] (Thixotropic value (yield stress value / plastic viscosity value))
[0049] As shown in Table 2, after adding the multifunctional shrinkage-reducing self-expanding rheological agent, the thixotropic properties, shrinkage properties and chloride ion penetration resistance of UHPC are greatly improved, the plastic viscosity is reduced by 62.7%, the yield stress is increased by about 3 times, the 7d shrinkage is reduced by 32.8%, and the chloride ion penetration resistance is increased by about 3 times.
[0050] The mix ratio of Comparative Example 2 is the same as that of Example 1, but the anticorrosion and shrinkage reducing component LDHs does not carry the biofilm, and the two materials of the anticorrosion and shrinkage reducing component, the biofilm and LDHs, are added in the same amounts as in Example 1. The results of the rheological properties, 7d shrinkage and chloride ion penetration resistance of UHPC are shown in Table 3.
[0051] Table 3 Results of plastic viscosity, yield stress, 7d shrinkage, chloride ion permeability resistance and thixotropic value of UHPC in Example 1 and Comparative Example 2
[0052]
[0053] As shown in Table 3, the thixotropic properties and shrinkage properties of Comparative Example 2 are not much different from those of Example 1, and have a significant effect on the resistance of concrete to chloride ion penetration, with the chloride ion permeability coefficient reduced by 37.5%, indicating that the lack of LDHs loading has a significant effect on the dispersibility of LDHs and reduces the adsorption capacity for chloride ions.
[0054] Embodiment 2-3
[0055] The mix ratios of Examples 2 and 3 are the same as those of Example 1, but the ratios of the composite rheological component, the swelling component, and the anti-corrosion shrinkage-reducing component in the multifunctional shrinkage-reducing self-expanding rheological agent are different. The ratio of the composite rheological component, the swelling component, and the anti-corrosion shrinkage-reducing component in Example 2 is 67:30:3. The ratio of the composite rheological component, the swelling component, and the anti-corrosion shrinkage-reducing component in Example 3 is 65:30:5. The results of the rheological properties, 7d shrinkage, and resistance to chloride ion penetration of UHPC are shown in Table 4.
[0056] Table 4 Results of plastic viscosity, yield stress, 7d shrinkage, chloride ion permeability resistance and thixotropic value of UHPC in Examples 1, 2 and 3
[0057]
[0058] As shown in Table 4, the rheological properties and shrinkage properties of Implementation 2 and Implementation 3 are similar to those of Implementation 1, but the chloride ion permeability coefficient is slightly reduced, indicating that when the anti-corrosion and shrinkage-reducing component is 4, the multifunctional shrinkage-reducing self-expanding rheological agent has the best anti-corrosion performance.
[0059] Comparative Examples 3 to 5
[0060] The mix ratios of Comparative Examples 3 to 5 are the same as those of Example 1, but there is no composite rheological component in the multifunctional shrinkage-reducing self-expanding rheological agent in Comparative Example 3, no expansion component in Comparative Example 4, and no anti-corrosion shrinkage-reducing component in Comparative Example 5. The results of the rheological properties, 7d shrinkage, and chloride ion penetration resistance of UHPC are shown in Table 5.
[0061] Table 5 Comparative Examples 3 to 5 UHPC plastic viscosity, yield stress, 7d shrinkage, chloride ion permeability coefficient and thixotropic value results
[0062]
[0063] As shown in Table 5, without the addition of composite rheological components, the thixotropic properties of UHPC are greatly reduced. At the same time, the influence of the expansion component on the shrinkage performance of concrete is greater than that of the anti-corrosion shrinkage reduction component. The shrinkage reduction capacity of the anti-corrosion shrinkage reduction component is about 50% of that of the expansion component. The anti-corrosion shrinkage reduction component is crucial to improving the durability of concrete.
[0064] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.
Claims
1. A multifunctional shrinkage-reducing self-expansion rheological agent for sprayed ultra-high performance concrete, It is characterized in that It includes composite rheological components, expansion components and anti-corrosion and shrinkage-reducing components; Among them, the composite rheological component is 65 to 87 parts, the expansion component is 10 to 30 parts, and the anti-corrosion and shrinkage-reducing component is 3 to 5 parts.
2. The multifunctional shrinkage-reducing self-expansion rheological agent for sprayed ultra-high performance concrete according to claim 1, It is characterized in that It is composed of a composite rheological component, an expansion component and an anti-corrosion and shrinkage-reducing component.
3. The multifunctional shrinkage-reducing self-expansion rheological agent for sprayed ultra-high performance concrete according to claim 1 or 2, It is characterized in that The composite rheological component includes manganese slag and cellulose ether; The ratio of manganese slag to cellulose ether is 98:2, and the specific surface area of manganese slag is 600-800m 2 / kg; cellulose ether is hydroxyethyl methyl cellulose ether with a molecular weight of 30,000 to 50,000.
4. The multifunctional shrinkage-reducing self-expansion rheological agent for sprayed ultra-high performance concrete according to claim 1 or 2, It is characterized in that The expansion component is a modified calcium oxide-calcium sulfoaluminate expansion agent, which is prepared from calcium oxide and calcium sulfoaluminate in a ratio of 7:
3.
5. The multifunctional shrinkage-reducing self-expansion rheological agent for sprayed ultra-high performance concrete according to claim 1 or 2, It is characterized in that The anti-corrosion and shrinkage-reducing component is a double-layered hydroxide-loaded biofilm.
6. The multifunctional shrinkage-reducing self-expansion rheological agent for sprayed ultra-high performance concrete according to claim 5, It is characterized in that The preparation method of the double metal layer hydroxide loaded biofilm is: S1. Preparation of biofilm; S2. Heat the biofilm in water to 70 to 85°C, then add M 3+ Solution and M 2+ solution, then adding NaOH solution to adjust the pH to 11-12, stirring thoroughly, centrifuging, washing to neutrality, and drying to obtain a double-metal hydroxide-loaded biofilm; wherein the M 3+ The solution includes FeCl 3 、AlCl 3 and CoCl 3 , M 2+ The solution includes CaCl 2 MgCl 2 and ZnCl 2 .
7. The multifunctional shrinkage-reducing self-expansion rheological agent for sprayed ultra-high performance concrete according to claim 6, It is characterized in that The preparation of the biofilm in S1 specifically includes: inoculating frozen Bacillus subtilis into Luria / Miller LB-Medium liquid at 37°C±2°C overnight; then transferring the culture to a shaking incubator to grow for 12±1 hours, and then smearing the liquid culture on an agar plate enriched with LBPlus medium, so that the Bacillus subtilis liquid culture produces a biofilm on the agar plate, and the biofilm is obtained after growing for at least 24 hours.
Citation Information
Patent Citations
Asymmetric solid waste-based ceramic catalytic membrane as well as preparation method and application thereof
CN115974528A
